SAT0574 Improving Timely Follow-Up after High Blood Pressures in Rheumatology Clinics Using Staff Protocols. (15th July 2016) - Bartels, C.M.; Ramly, E.; Johnson, H.; McBride, P.; Li, Z.; Zhao, Y.; Lewicki, K.; Lauver, D.
Abstract : Background: Hypertension (HTN) is the most prevalent cardiovascular disease (CVD) risk factor among adults with rheumatic conditions. However, we found that blood pressures were addressed in <1/3 of rheumatology visits, even when severely elevated (≥160/100 mmHg). At this range, only 11 patients need to be treated for HTN to prevent one CVD event. In primary care, HTN protocols executed by nurses (RNs) or medical assistants (MAs) during vital sign assessment have improved control of high blood pressure (BP). Yet, such protocols have not been tested in rheumatology clinics. Objectives: Our objective was to study the feasibility and impact of an intervention using a staff HTN protocol to facilitate timely (<4 wks per Medicare quality measure) primary care follow-up for patients with high blood pressures at rheumatology visits. Methods: We conducted a pre-post study in three academic rheumatology clinics. All eligible adult (≥18 years-old) rheumatology visits with BP ≥140/90 mmHg (12/2014–5/2015) were compared to pre-intervention visits (2012–9/2014). Our multi-dimensional intervention included: (1) educating staff on HTN, rheumatologic diseases, and CVD risk, (2) electronic health record (EHR) alerts for staff to re-measure BPs if ≥140/90 and 3) cuing brief patient education and scheduling primary care follow-up if 2nd BP ≥140/90, and (4) monthly audit and feedback with staff about performance. We assessed timely primary care follow-up of high BPs among patients who received primary care in our system using EHR data. We performed multivariable logistic regression and compared the odds (OR, 95%CI) of timely primary care follow-up before and during intervention, while controlling for baseline socio-demographics, comorbidities, utilization, and clinic. Results: We compared 689 intervention period visits to 4, 683 pre-intervention visits with BPs ≥140/90. Patient groups were comparable before and during intervention. Staff initiated BP re-measurement in 80% of eligible visits during intervention months 4–6, compared to <1% pre-intervention; overall improvement 60%, p<0.001. More patients received timely primary care follow-up for HTN during the intervention, (44%, vs 29% before, p=0.0003). Multivariable analysis showed that eligible visits during the intervention had two-fold higher odds of timely follow-up compared to pre-intervention, OR 2.1, 1.4–3.0 (p<0.0001). We observed positive associations between timely follow-up and race (black vs. white OR 1.7, 1.1–2.5) and diabetes (vs. no diabetes OR 1.3, 1.01–1.6) post intervention. Conclusions: Our intervention was feasible for usual rheumatology clinic staff and it doubled rates of timely BP follow-up. Future studies should examine this intervention in other rheumatology clinics, and its impact on HTN control to reduce CVD risk in rheumatology patients. Disclosure of Interest: C. Bartels Grant/research support from: Independent Grants for Learning and Change (Pfizer), E. Ramly: None declared, H. Johnson: None declared, P. McBride: None declared, Z. Li: None declared, Y. Zhao: None declared, K. Lewicki: None declared, D. Lauver: None declared